2004
DOI: 10.1152/ajpgi.00348.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protection from ischemic liver injury by activation of A2Aadenosine receptors during reperfusion: inhibition of chemokine induction

Abstract: Ischemia-reperfusion (I/R) injury occurs as a result of restoring blood flow to previously hypoperfused vessels or after tissue transplantation and is characterized by inflammation and microvascular occlusion. We report here that 4-{3-[6-amino-9-(5-ethylcarbamoyl-3,4-dihydroxy-tetrahydro-furan-2-yl)-9H-purin-2-yl]-prop-2-ynyl}-cyclohexanecarboxylic acid methyl ester (ATL146e), a selective agonist of the A2A adenosine receptor (A2AAR), profoundly protects mouse liver from I/R injury when administered at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
120
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 49 publications
(41 reference statements)
11
120
1
1
Order By: Relevance
“…The decreased neutrophil migration in the lung is believed to be related to the anti-inflammatory properties of CGS-21680 in the treated groups (41,42). Furthermore, the transient higher MAP values observed in the CGS-21680-treated animals may be due to preserved vascular integrity for a given amount of fluids infused in all animals.…”
Section: Discussionmentioning
confidence: 94%
“…The decreased neutrophil migration in the lung is believed to be related to the anti-inflammatory properties of CGS-21680 in the treated groups (41,42). Furthermore, the transient higher MAP values observed in the CGS-21680-treated animals may be due to preserved vascular integrity for a given amount of fluids infused in all animals.…”
Section: Discussionmentioning
confidence: 94%
“…56 Indeed, a serious of previous investigations from the laboratory of Dr. Okusa had shown that activation of Adora2a receptors on T cells provides protection during acute ischemic kidney disease. 2,3,21,22,57,58 As such, it is conceivable that Adora2a receptors expressed on inflammatory cells and vascular Adora2b receptors function together to protect the kidneys during diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, adenosine is a potent anti-inflammatory agent with A 2A Rs triggering BOFF^signals in activated immune cells, which constitutes one of the most fundamental and immediate tissue-protecting mechanisms (reviewed in [295,296]). A 2A R agonists were even named Bthe most potent anti-inflammatory drug known to mankind.^Ac-cordingly, activation of A 2A Rs has been shown to confer a robust protection against tissue damage from ischemiaYreperfusion injury in different organ such as heart [297Y299], blood vessels [300], kidney [301,302], liver [303,304], lung [305,306], joints [307], skin [308,309], and even in the spinal cord [310,311] and in the brain following hemorrhage [312] or acute infection [313]. Thus, it is the activation (rather the blockade) of A 2A Rs that confers protection against damage triggered by inflammation in peripheral tissues, precisely the opposite of what is observed in the damaged adult brain.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%